Customer-based brand equity model for the Shariah-compliant tourism: A conceptual study from the international Muslim tourist perspective - Haque, A. K. M. Ahasanul; Ahmed, Faruk; Abdullah, Kalthom; Razali, Siti Salwani (2016)
The authors develop a conceptual model of consumer-based brand equity for the Shariah-compliant tourism from the international Muslim tourist perspective in Malaysia. This model might aid concerned users to understand and measure the Shariah-compliant brand image and equity developed in the Muslim customers’ mind regarding quality from Islamic perspective, Islamic brand identity and personality, haram-halal, Makhru, and devotion to God. Fundamentally it is Islamic value based brand image and equity development concept which is different from a platform of building image and equity from the contemporary ethical marketing. Positive customer-based brand equity entices consumers to buy products or service and the vice versa. Shariah-compliant brand image is a different set of dimensions like brand equity as supported by Shariah-law, whereas in the conventional brand knowledge, favorableness is considered as an important dimension (Keller 2003); that is, only brand image as a main element of knowledge is conceptualized in this model because Islam does not priotize personal favorableness violating Shariah law. Different media channels (Traditional channel-based and Modern channel-based integrated Marketing communication) injecting Shariah-complaint message of tourism into International Muslim tourists based on Shariah-compliant tourism create Shariah-complaint consumer-based brand equity. Instruments appropriate for measuring customer-based brand equity are implied and, possible future research is discussed as well.